The Role of Shrimp Breeding Innovation in Improving Aquaculture Productivity and Fisheries Business Sustainability in Sumbawa, West Nusa Tenggara - Sabil Mokodenseho; Erwina Kartika Devi; Yana Priyana (Westscience Press, 2023)
The aquaculture sector has come to be recognized as a key engine of both economic growth and seafood production worldwide. Shrimp farming in particular, and aquaculture in general, are major contributors to local livelihoods and food security in Sumbawa, West Nusa Tenggara, Indonesia. However, as this industry expands, it will have to contend with issues pertaining to productivity, sustainability of the environment, and the long-term viability of the fishing industry. Innovations in shrimp breeding have been implemented in the area to solve these problems. The various effects of these advances on aquaculture productivity and the long-term viability of Sumbawa's fishing enterprises are examined in this qualitative investigation. The results show how innovation, productivity, sustainability, and the particular socio-environmental setting of the area interact in a complicated way. Shrimp growth and disease resistance have increased thanks to selective breeding techniques, but genetic manipulation is still up for discussion. Sustainable feed methods are a viable way to lessen the impact on the environment. Effective disease management, together with market access and adherence to international quality standards, are critical components of a sustainable fisheries enterprise. This study promotes sustainable aquaculture methods and the long-term success of Sumbawa's fishing enterprises by offering useful insights and suggestions.